Effect of mannitol on brain metabolism and tissue oxygenation in severe haemorrhagic stroke. Issue 4 (30th September 2010) - Helbok, Raimund; Kurtz, Pedro; Schmidt, J Michael; Stuart, R Morgan; Fernandez, Luis; Malhotra, Rishi; Presciutti, Mary; Ostapkovich, Noeleen D; Connolly, E Sander; Lee, Kiwon; Badjatia, Neeraj; Mayer, Stephan A; et al.
Abstract : Background: The impact of osmotic therapies on brain metabolism has not been extensively studied in humans. The authors examined if mannitol treatment of raised intracranial pressure will result in an improvement in brain metabolism together with the expected drop in intracranial pressure (ICP). Methods: This is a retrospective review of prospectively collected data. Twenty episodes of raised ICP (>20 mm Hg) resistant to standard therapy that required infusions of mannitol were studied in 12 comatose patients with multimodality monitoring including ICP, PbtO2 and microdialysis. The authors compared mean arterial blood pressure, ICP, cerebral perfusion pressure, PbtO2, brain lactate, pyruvate and glucose using cerebral microdialysis, for 3 h preceding and 4 h after hyperosmolar therapy. Time-series data were analysed using a multivariable general linear model utilising generalised estimating equations for model estimation to account for within-subjects and between-subjects variations over time. Results: 20% mannitol solution (1 g/kg) was administered at the discretion of the attending neurointensivist. ICP decreased 30 min (from 27±13 to 19±16 mm Hg, p<0.001) and cerebral perfusion pressure increased 45 min (from 73± 18 to 85±22 mm Hg, p=0.002) after the start of mannitol infusions, whereas mean arterial blood pressure and PbtO2 did not change significantly. The peak lactate–pyruvate ratio was recorded at the time of initiating osmotherapy (44±20) with an 18% decrease over 2 h following mannitol therapy (35±16; p=0.002). Brain glucose remained unaffected. Conclusions: Mannitol effectively reduces ICP and appeared to benefit brain metabolism as measured by the lactate–pyruvate ratio.